The correlation between porosity characteristics and the crystallographic texture in extruded stabilized aluminium titanate for diesel particulate filter applications. Issue 4 (April 2020) - Chen, Cong; Müller, Bernd R.; Prinz, Carsten; Stroh, Julia; Feldmann, Ines; Bruno, Giovanni
Abstract: Porous ceramic diesel particulate filters (DPFs) are extruded products that possess macroscopic anisotropic mechanical and thermal properties. This anisotropy is caused by both morphological features (mostly the orientation of porosity) and crystallographic texture. We systematically studied those two aspects in two aluminum titanate ceramic materials of different porosity using mercury porosimetry, gas adsorption, electron microscopy, X-ray diffraction, and X-ray refraction radiography. We found that a lower porosity content implies a larger isotropy of both the crystal texture and the porosity orientation. We also found that, analogous to cordierite, crystallites do align with their axis of negative thermal expansion along the extrusion direction. However, unlike what found for cordierite, the aluminium titanate crystallite form is such that a more pronounced (0 0 2) texture along the extrusion direction implies porosity aligned perpendicular to it.